The lncRNA TEX41 is upregulated in pediatric B-Cells Acute Lymphoblastic Leukemia and it is necessary for leukemic cell growth - Francesca Maria Orlandella; Giovanni Smaldone; Giuliana Salvatore; Luigi Vitagliano; Alessandra Cianflone; Rosanna Parasole; Giuliana Beneduce; Giuseppe Menna; Marco Salvatore; Peppino Mirabelli (BMC, 2021)
Abstract Background Long non-coding RNAs (lncRNAs) represent a diverse class of RNAs involved in the regulation of various physiological and pathological cellular processes, including transcription, intracellular trafficking, and chromosome remodeling. LncRNAs deregulation was linked to the development and progression of various cancer types, such as acute leukemias. In this context, lncRNAs were also evaluated as a novel class of biomarkers for cancer diagnosis and prognosis. Here, we analyzed TEX41 in childhood B cell acute lymphoid leukemia (B-ALL). Methods Total RNA was extracted from pediatric B-ALL patients (at diagnosis and after induction of therapy) and from healthy subjects. Total RNA was also extracted from different leukemia cell line models. The expression level of TEX41 was evaluated by q-RT-PCR. Also, the dataset deposited by St. Jude Children's Research Hospital was consulted. Furthermore, the silencing of TEX41 in RS4;11 cell line was obtained by 2'-Deoxy, 2'Fluroarabino Nucleic Acids (2'F-ANAs) Oligonucleotides, and the effect on cell proliferation was evaluated. Cell cycle progression and its regulators were analyzed by flow cytometry and immunoblotting. Results We exploited the St Jude Cloud database and found that TEX41 is a lncRNA primarily expressed in the case of B-ALL (n = 79) while its expression levels are low/absent for T-cell ALL (n = 25) and acute myeloid leukemia (n = 38). The association of TEX41 with B-ALL was confirmed by real-time PCR assays. TEX41 disclosed increased expression levels in bone marrow from patients with B-ALL at diagnosis, while its expression levels became low or absent when retested in Bone Marrow cells of the same patient after 1 month of induction therapy. Also, silencing experiments performed on RS4;11 cells showed that TEX41 downregulation impaired in vitro leukemic cell growth determining their arrest in the G2-M phase and the deregulation of cell cycle proteins. Conclusions Our findings highlight that TEX41 is an upregulated lncRNA in the case of B-ALL and this feature makes it a novel potential biomarker for the diagnosis of this leukemia subtype in pediatric patients. Finally, TEX41 expression seems to be critical for leukemic proliferation, indeed, silencing experiments targeting TEX41 mRNA in the RS4;11 cell line hampered in vitro cell growth and cell cycle progression, by inducing G2-M arrest as confirmed propidium iodide staining and by the upregulation of p53 and p21 proteins.